2019
DOI: 10.18203/2349-2902.isj20192098
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on obstructed inguinal hernia: a descriptive study on 53 cases

Abstract: Background: Inguinal hernias are the common causes of surgical admissions and referral of patients from primary physicians. Although we have made a great progress in treating hernia the management of its complications has progressed only a little. The aim of study was to determine the various modes of presentation, clinical features, diagnostic and therapeutic strategies and to evaluate the post-operative outcome in obstructed hernia surgeries.Methods: After obtaining written and informed consent from the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Wound infection and ileus were also observed, especially in cases of strangulation and where bowel resection was performed. A similar trend was observed in other studies [21]. We observed that patients with primary hernia developed postoperative complications more than patients with recurrent hernia and this may be due to the larger number of patients with primary hernia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Wound infection and ileus were also observed, especially in cases of strangulation and where bowel resection was performed. A similar trend was observed in other studies [21]. We observed that patients with primary hernia developed postoperative complications more than patients with recurrent hernia and this may be due to the larger number of patients with primary hernia.…”
Section: Discussionsupporting
confidence: 91%
“…These cases were managed via open reduction of the contents and the modified Bassini's repair technique. Those with obstructed (33.33%) and strangulated (6%) hernias were also managed via open surgery and resection with end-to-end anastomosis of the unhealthy bowel segments as well as via modified Bassini's repair without mesh; this is also consistent with the findings of other studies [21].…”
Section: Discussionsupporting
confidence: 87%
“…Femoral hernias have tight unyielding hernial rings whereas direct inguinal hernias have no well-defined hernial ring. 17 Present study found that pain and swelling were reported in all the cases, after that vomiting (58%) was the most common clinical presentation followed by abdominal distension (40%).…”
Section: Discussionmentioning
confidence: 54%
“…21 The nature of contents of a complicated hernial sac is important in two respects: the anatomical structure involved and its viability. 17 Present study found that most common content of hernial sac was small bowel (54%) followed by omentum (34% mesh could be safely and effectively used in patients with incarcerated or strangulated inguinal hernia, which significantly reduced the risk of hernia recurrence but did not increase the opportunity of surgical site infection. 14,15,19,20,37,38 Cases operated by 'resection and anastomosis' had reported 1 case with leak,…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation